2014
DOI: 10.1016/j.bbamem.2014.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Modular analysis of hipposin, a histone-derived antimicrobial peptide consisting of membrane translocating and membrane permeabilizing fragments

Abstract: Antimicrobial peptides continue to garner attention as potential alternatives to conventional antibiotics. Hipposin is a histone-derived antimicrobial peptide (HDAP) that was previously isolated from Atlantic halibut. Though its potency against several bacterial strains has been documented, its antibacterial mechanism had not been characterized. The mechanism of this peptide is particularly interesting to consider since the full hipposin sequence contains the sequences of parasin and buforin II (BF2), two othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…However, with spheroplasts we can consider the percentage of images showing translocation or membrane localization, providing more systematic data (Table 1). Again, these percentages support the previously observed trends for membrane entry (5,6,16), with BF2 and HipC entering significantly more spheroplasts than P11A BF2 and magainin. Interestingly, none of these peptides exclusively exhibit membrane localization or membrane translocation behavior.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…However, with spheroplasts we can consider the percentage of images showing translocation or membrane localization, providing more systematic data (Table 1). Again, these percentages support the previously observed trends for membrane entry (5,6,16), with BF2 and HipC entering significantly more spheroplasts than P11A BF2 and magainin. Interestingly, none of these peptides exclusively exhibit membrane localization or membrane translocation behavior.…”
supporting
confidence: 79%
“…Thus, it has become increasingly important for researchers to reliably determine whether AMPs are able to effectively translocate into bacterial cells (3). Many researchers have turned to confocal microscopy in order to assess cell entry (4)(5)(6)(7)(8)(9)(10)(11). However, bacterial cells are so small that effective imaging is limited by the resolution of conventional light microscopes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…27, 37-39 To form experimental vesicles, lipids dissolved in chloroform at a 75:20:5 ratio of POPC:POPG:DNS-PE were dried and reconsituted in a 1:1 volume mixture by volume of 10 mM HEPES buffer and 0.4 mM trypsin in 10 mM HEPES buffer solution for a final concentration of 0.2 mM trypsin. For control vesicles, Bowman-Birk Inhibitor was added to the reconstitution mixture for a final concentration of 2.0 mM.…”
Section: Methodsmentioning
confidence: 99%
“…A slightly larger N-terminal cleavage product (51 aa) of histone H2A, known as hipposin I, was discovered in Atlantic halibut [34]. A recent study found that the N-terminal domain of hipposin is responsible for bacterial membrane permeabilization and killing, while a C-terminal fragment (termed HipC) can enter cells without killing the bacteria [59]. Such studies raise interest in the potential of selective use of fragments of histones, or novel combinations of histone fragments, for antimicrobial therapy as proposed by Kawasaki et al [55].…”
Section: Cleavage Products Of Histonesmentioning
confidence: 99%